2020
DOI: 10.1001/jamanetworkopen.2020.7221
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Occult Spinal Dysraphism Among Infants With Cutaneous Stigmata and Proportion Managed With Neurosurgery

Abstract: IMPORTANCE Occult spinal dysraphism (OSD) is the most common congenital spinal anomaly.Cutaneous anomalies such as skin dimples or deviated gluteal folds are well known as stigmata of OSD and are indicators for further evaluation; however, the association between cutaneous anomalies and OSD has not been systemically evaluated.OBJECTIVE To evaluate the incidence of OSD and the proportion of OSD cases managed with a neurosurgical intervention among neonates or infants with various cutaneous stigmata.DATA SOURCES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
1
24
1
2
Order By: Relevance
“…2 Studies generally concur that an infant with >1 LsCM increases the likelihood of OSD. 3,[10][11][12] We previously reported a 3 ½-year study (1 March 2015-30 September 2018) of 67 infants with at least one LsCM who were evaluated in our pediatric urology clinic. 13 The most common LsCMs were duplicated or bifurcated gluteal folds (46%) and gluteal asymmetry (16%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Studies generally concur that an infant with >1 LsCM increases the likelihood of OSD. 3,[10][11][12] We previously reported a 3 ½-year study (1 March 2015-30 September 2018) of 67 infants with at least one LsCM who were evaluated in our pediatric urology clinic. 13 The most common LsCMs were duplicated or bifurcated gluteal folds (46%) and gluteal asymmetry (16%).…”
Section: Introductionmentioning
confidence: 99%
“…In children with OSDs, lumbosacral cutaneous manifestations (LsCMs) are observed in 51%-100% patients. [1][2][3][4][5] One type of OSD, tethered cord syndrome (TCS), may lead to neurological, gastrointestinal, musculoskeletal, and urinary dysfunction due to spinal cord traction. [6][7][8][9] Timely diagnosis and treatment of TCS may mitigate the devastating sequelae that may ensue.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Singh 2003 reported that out of 155 patients of spinal dysraphism, the male to female ratio was 1.5:1. Spinal dysraphism was found to be more prevalent in infants (Choi et al, 2020). In the current study, the maximum number of patients belonged to neonatal age group.…”
Section: Discussionmentioning
confidence: 42%
“…However, the wide variation in the morphological appearances of the lumbosacral and coccygeal regions along with the sparsity of the literature regarding the predictive value of these variations, creates a diagnostic dilemma when it comes to screening neonates [9]. On the contrary, a vast majority of patients (about 50-80%) with SD are presented with cutaneous stigmata, as documented by Shields et al [20] and Choi et al [22]. This was in concordance with the 55% confronted in our study cohort.…”
Section: Discussionmentioning
confidence: 99%